PENGEMBANGAN KEAMANAN SISTEM INFORMASI SST (SELF SERVICE TERMINAL) STMIK PRADNYA PARAMITA MALANG - Widarti, Dinny Wahyu; Arifin, Samsul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Information System Security is essential to ensure the proper functioning of the information system. Weak information system security may result that other people who do not have the right can be entered into the system information without passed the security and perform activities that can damage or destroy data on the information system, even can destroy that information system itself. On one side, security of the information system needs to be improved, like in login process to get into the information system. Login process becames a tool to pave the ways for someone to infiltrate into the information system. There are several ways to do so that login process to be secure, such as anti SQL Injection and Verification login with SMS Gateway. Expected by using the login process with anti SQL Injection and Verification login with SMS Gateway can reduce the occurrence of fraud against Information Systems in STMIK PPKIA Pradnya Paramita Malang.Â Keywords: Security, Information Systems, and SMS Gateway